The Relationship between Personality Traits and Anxiety with the Mediating Role of Desire for Fame among TikTokers (Al-Qamar, 2024)
The main aim of this study was to explore the relationship between personality traits (extraversion, agreeableness, conscientiousness, emotional stability, and openness to experiences) and anxiety with the mediating role of desire for fame among TikTokers. For this purpose, cross-sectional research was conducted on the sample of 205 male and female young adults using purposive sampling technique. Ten Item Personality Inventory, Hamilton Anxiety Measure scale, and Desire for Fame scale were used to measure the variables. Results showed a significant positive association between Extraversion and Desire for fame, while a non-significant relationship with anxiety. It showed a significant positive relationship between Agreeableness, anxiety and desire for fame. Conscientiousness shows a significantly positive relationship with anxiety and desire for fame. Emotional stability is significantly positively related to anxiety and desire for fame. Openness shows a significantly positive correlation with anxiety and desire for fame. Furthermore, a significant positive correlation exists between anxiety and desire fame. The t-test results showed that there will be a gender difference in extraversion trait, agreeableness trait and openness to experience trait. There is no statistically significant difference in terms of area (urban and rural). Individuals with age range 18-21 reported higher anxiety as compared to the 22-24 and 25-28 age ranges. Desire for fame appeared to fully mediate the path between personality traits and anxiety. These findings fill the research gap and have practical implications in the area of psychological health concerns and social media use.
Keywords: Personality traits; Desire for fame; Anxiety